Impact of ambient air pollution on physical activity engagement among university students - Wangsan, Kampanat; Panumasvivat, Jinjuta; Usanakul, Thiti; Sirivoravith, Vorapat; Rojanachai, Supanut; Zheng, Natchaphol; Boontan, Chonlathee; Sapbamrer, Ratana (Frontiers in Public Health, 2024)
IntroductionPM2.5 poses significant health risks with prolonged exposure, potentially reducing physical activity levels. This study aims to investigate the impact of ambient PM2.5 levels on physical activity engagement among individuals.MethodsThe retrospective cross-sectional study involved 423 students from Chiang Mai University residing there between January and August 2023. We used the validated Thai version of the International Physical Activity Questionnaire to assess physical activity intensity during high and low pollution periods. Individuals who engage in at least 150 min of moderate-intensity or 75 min of high-intensity physical activity per week meet the recommended physical activity guidelines. Multiple logistic regression analyzed air pollution's relation to physical activity intensity, and Cochran's Q-test compared activity levels across pollution periods.ResultsRecommended physical activity prevalence was 76.36% during high PM2.5 and 71.63% during low PM2.5 periods, it showed higher physical activity during polluted periods (p = 0.049). Individuals' behavior showed a preference for indoor exercise (p < 0.001), consistent PM2.5 level checks (p < 0.001) during high PM2.5 periods. Internal motivation significantly associated with recommended physical activity in both low and high PM2.5 periods (aOR = 2.46, 95% CI = 1.14 – 5.27 and aOR = 4.00, 95% CI = 1.84 – 8.70, respectively). The outdoor exercise significantly associated with the recommended physical activity only during the low PM2.5 period (aOR = 1.72, 95% CI = 1.03 – 2.87).ConclusionUniversity students showed increased physical activity intensity during high PM2.5 periods, favoring indoor exercise in polluted environments. This behavioral shift highlights environmental pollution's influence on lifestyle choices and cornering on health outcomes. Government and university support is crucial for implementing measures to mitigate PM2.5 pollution, including promoting safe indoor exercise, enhancing pollution control measures, and developing air quality monitoring and warning systems.